Our Children's Literature Under the Microscope - Salma Atallah (Sultan Qaboos University, 2018)
The literature of children is characterized by the privacy of adhesion to the name of the recipient, and by portraying ideas, feelings, experiences and imaginations that agree with their recognitions and reflect  their linguistic, intellectual and emotional level. Because literature is in this status of importance in our lives and the lives of our children, it was necessary to read in reality and visions, starting from some statistics and previews. We have found that it is relatively weak and few, and even suffers a crisis of existence, for many reasons, ranging from ideological to educational and academic. Factors include the tyranny of materialism and digital culture on Arabic human life, the breakdown of the linguistic power and the loss of identity, the outbreak of conflicts and wars, as well as the non-permanent presence of the favorable environment and the deviation of some educational approaches because of the lack of creative writers, and the association of this literature with non-free educational axes, the adoption of difficult models and curricula with topics that are consumed and sometimes denied, and the wrong approaches and methodologies that are limited to mere understanding, indoctrination and non-systematic explanation. The Arab countries must overcome individual initiatives and develop a comprehensive national and educational policy that reinforces the human sciences from the margin of life to its center, giving the Arabic language the necessary importance, activating the role of culture, securing the supportive environment, and developing malleable programs and methodologies that consider life issues, and the need for regularity of literature in a correct and good course by focusing on modern theories such as active, self-learning, differentiated and indirect, as well as modern monetary theories and communication, functional, interactive and logical trainings.